An Insightful Experiences - The, Star (The Star, 2014)
AeU aims to focus on Asian businesses in a global context. " I find the curriculum that incorporates estern and western perspectives with a special attention to Asian business perspectives highly relevant to my goal of becoming a knowledgeable and competent Asian business leader." said by Tuan Mohamed Anif Sallay